A colorimetric and ratiometric dual-site fluorescent probe with 2, 4-dinitrobenzenesulfonyl and aldehyde groups for imaging of aminothiols in living cells and zebrafish. (September 2018) - Wang, Yi; Wang, Lijun; Jiang, Erkang; Zhu, Meiqing; Wang, Zhen; Fan, Shisuo; Gao, Qian; Liu, Shangzhong; Li, Qing X.; Hua, Rimao
Abstract: Aminothiol levels are indicative of cellular and physiological statuses. A colorimetric and ratiometric dual-site fluorescent probe, NL-S, has been designed and synthesized.NL-S contains both a 2, 4-dinitrobenzenesulfonyl group and an aldehyde group as recognition units for aminothiols.NL-S exhibited highly selective and sensitive detection of aminothiols, with a 27–44-fold enhancement of the fluorescent signal observed within 30 min of the addition of up to 20 equiv. of cysteine (Cys), homocysteine (Hcy) or glutathione (GSH) in aqueous media. The probe undergoes a turn-on excited-state intramolecular proton transfer process derived from cleavage and condensation reactions. The limits of detection for Cys, Hcy and GSH were 0.114, 0.146 and 0.202 μM, respectively.NL-S with negligible cytotoxicity was successfully employed to fluorescent imaging of aminothiols in living cells and zebrafish, suggesting good potential ofNL-S in biological applications. Graphical abstract: Highlights: A novel ratiometric and colorimetric dual-site fluorescent probe was described. The probe could detect aminothiols in DMSO-HEPES buffer solution. The assay was successfully applied in living cell and zebrafish tissue imaging.